DEGRO practical guidelines for radiotherapy of breast cancer VI: therapy of locoregional breast cancer recurrences - Harms, Wolfgang; Budach, W.; Dunst, J.; Feyer, P.; Fietkau, Rainer; Haase, W.; Krug, D.; Piroth, M. D.; Sautter-Bihl, Marie-Luise; Sedlmayer, F.; Souchon, R.; Wenz, F.; et al. (Strahlentherapie und Onkologie, 2016)
To update the practical guidelines for radiotherapy of patients with locoregional breast cancer recurrences based on the current German interdisciplinary S3 guidelines 2012.A comprehensive survey of the literature using the search phrases "locoregional breast cancer recurrence", "chest wall recurrence", "local recurrence", "regional recurrence", and "breast cancer" was performed, using the limits "clinical trials", "randomized trials", "meta-analysis", "systematic review", and "guidelines".Patients with isolated in-breast or regional breast cancer recurrences should be treated with curative intent. Mastectomy is the standard of care for patients with ipsilateral breast tumor recurrence. In a subset of patients, a second breast conservation followed by partial breast irradiation (PBI) is an appropriate alternative to mastectomy. If a second breast conservation is performed, additional irradiation should be mandatory. The largest reirradiation experience base exists for multicatheter brachytherapy; however, prospective clinical trials are needed to clearly define selection criteria, long-term local control, and toxicity. Following primary mastectomy, patients with resectable locoregional breast cancer recurrences should receive multimodality therapy including systemic therapy, surgery, and radiation +/- hyperthermia. This approach results in high local control rates and long-term survival is achieved in a subset of patients. In radiation-naive patients with unresectable locoregional recurrences, radiation therapy is mandatory. In previously irradiated patients with a high risk of a second local recurrence after surgical resection or in patients with unresectable recurrences, reirradiation should be strongly considered. Indication and dose concepts depend on the time interval to first radiotherapy, presence of late radiation effects, and concurrent or sequential systemic treatment. Combination with hyperthermia can further improve tumor control. In patients with isolated axillary or supraclavicular recurrence, durable disease control is best achieved with multimodality therapy including surgery and radiotherapy. Radiation therapy significantly improves local control and should be applied whenever feasible.
EVALuna2:18354